Exploración y desarrollo de modelos estadísticos de calidad del aire para la ciudad de bogotá D.C. (2017)
"The objective of the project was to explore the applicability of simple statistical models, such as the ARIMA, for the forecasting of levels of atmospheric particulate matter (PM10) in different areas of the city of Bogotá in relation to the historical record of concentrations of the Network Of Measurement of Air Quality of the Colombian capital (RMCAB). First we investigated how to correctly create this kind of models. Subsequently an analysis was made to the RMCAB database to find the time series to be modeled. Finally, models were applied to the found time series of particulate material of the RMCAB to evaluate both its predictive capacity and its applicability." -- Tomado del Formato de Documento de Grado.